THE 'WHO AND WHY' OF LOTTERY: EMPIRICAL HIGHLIGHTS FROM THE SEMINAL ECONOMIC LITERATURE. (10th May 2012) - Perez, Levi; Humphreys, Brad
Abstract: Lotteries operate today in many countries around the world. This type of gambling is usually run by governments and is sometimes described as regressive. Lottery is an unfair bet, so explaining the purchase of lottery tickets by risk‐averse consumers has been a challenge for economic theory. Lotteries can be analysed from either of two economic perspectives: as a source of public revenue or as a consumer commodity. In this paper the state of economic research on lotteries is reviewed, focusing on its main empirical findings.